EFFECT OF SUSTAINABILITY REPORTING ON THE CASHFLOW PERFORMANCE OF LISTED OIL AND GAS FIRMS IN NIGERIA (Journal of Global Accounting, 2024)
The study examined the effect of sustainability reporting on the cashflow performance of listed oil and gas firms in Nigeria. The specific objective was to examine the effect of economic reporting, social reporting and environmental reporting on cashflow performance of listed oil and gas firms in Nigeria. Ex-post facto research design was used in the study. Out of a population of eleven (11) listed oil and gas firms in Nigeria, purposive sampling was used to select a sample of nine (9) firms. Data were collected from the annual reports of the sampled firms for a period of eleven years, which spanned from 2012 to 2022. Descriptive analysis was conducted while the hypotheses were tested using Robust Least Square regressions. The findings showed that: environmental reporting has a significant and negative effect on the cashflow performance of listed oil and gas firms in Nigeria (p-value = 0.0000); social reporting has a significant and positive effect on the cashflow performance of listed oil and gas firms in Nigeria (p-value = 0.0038). In conclusion, while environmental reporting may pose challenges due to its association with high compliance costs and regulatory scrutiny, social and economic reporting can enhance a firm’s reputation, stakeholder relations, and overall financial stability.
Keywords: Cashflow Performance; Environmental Reporting; Economic Reporting; Social Reporting